Marcadores de acesso a procedimentos de alta complexidade em cardiologia - Casarin, Rodrigo Guerra (2024)
Cardiovascular diseases represent the highest mortality rate in Brazil, and such pathologies result from complex factors, whether individual or institutional. Thus, the objective of this dissertation was to understand access to high-complexity cardiology procedures for people from rural and urban backgrounds. The proposed study is characterized as qualitative, descriptive, exploratory, and prospective. It was conducted at a large philanthropic hospital institution in the Northern region of Rio Grande do Sul, accredited as a high-complexity cardiology service within the Unified Health System (SUS). Data collection was carried out through semi-structured interviews, and the data were subjected to content analysis. Mindful of the ethical importance, the principles contained in Resolution No. 466/2012, which establishes defining criteria for research involving human subjects, were utilized as the foundation. Twenty-five patients were interviewed, with 13 residing in rural areas and 12 in urban areas. The results were presented in the form of an article, revealing two categories: I - Initial evidence: signs, symptoms, and outcomes; II - Paths and pitfalls of access to high-complexity cardiology procedures. The study made it evident that social, economic, and health factors play a crucial role in determining equitable access to cardiac services. Therefore, the construction of effective access to high-complexity cardiac procedures requires an approach that transcends clinical barriers, addressing the underfunding of SUS and confronting social markers of difference.